Trilha divertida dos capitéis de Nova Palma (RS): a educação patrimonial na educação infantil - Marchesan, Alexandra Pozzatti (2023)
The Italian immigrants, who settled in the Fourth Colony of Italian Immigration in Rio Grande do Sul, today Geopark Fourth Colony, inherited from their ancestors religious practices that were adapted to the localities where they started to live. In this study, we highlight religiosity from the construction of capitals, small chapels dedicated to a saint of devotion erected on the side of roads or at crossroads. In the city of Nova Palma/RS, 40 examples were built in the interior and central region, which denotes the importance of religiosity in this community. Therefore, this research entitled “Fun Trail of the Capitals of Nova Palma (RS): Heritage Education in Early Childhood Education”, linked to the Concentration Area and Research Line History and Cultural Heritage of the Professional Master's Degree in Cultural Heritage of the Federal University of Santa Maria (UFSM), aims to identify the historical context of the ten capitals most known by the children of the kindergarten from the Municipal School of Infantile Education Aquarela, in Nova Palma, as well as the one belonging to the Holy Trinity Church. In this way, the recognition of the importance of capitals as the heritage of Nova Palma is based on the history of the Mother Church to build a didactic resource for heritage education in early childhood education through play, a game in the form of a trail and a booklet for coloring. For this purpose, photographs and documents from the Nova Palma Genealogical Research Center, Geopark Fourth Colony, are used as sources. The trail game represents the route taken by devotees to the capitals of Nova Palma, a local tradition, whose route starts from the Holy Trinity Church towards ten of the 40 capitals. This choice is related to the participation of the children and their families, where the capitals most known to them stand out, thus justifying the methodological proposal adopted in this work, which is active research, where the subjects involved participate in a collaborative way. That said, we believe that the game proposed here will awaken the children curiosity to know the meaning of capitals, as well as to value the preservation of these heritage assets that identify the religiosity of immigrants and their descendants. Thus, heritage education as an educational resource will help children to become protagonists of their own history, as well as of the social group they are part of, improving their selfesteem and consciously enjoying the cultural assets that their ancestors left behind, making them become responsible citizens for the preservation and enhancement of the capitals of Nova Palma.